Penerapan Model Mind Mapping untuk Meningkatkan Keterampilan Menulis Karangan Narasi Siswa Sekolah Dasar - Nasri Yoni; Nurmalina Nurmalina; Molli Wahyuni (Journal on Education, 2022)
This research originates from the fact that many Grade IVA SD students have difficulty writing narrative essays in Indonesian. This is because the teacher does not provide variations in applying learning models that are less attractive. One solution to overcome this problem is to use a mind mapping model. This classroom action research aims to describe the improvement in narrative writing skills of class IVA students at SD Negeri 002 Kunto Darussalam. This research was carried out in two cycles with the subjects of this study being 22 class IVA students. Data collection techniques used in this research are documentation, observation, and test techniques. Based on the results of the study it can be concluded that in the first cycle the teacher's activity got an average percentage of 70% and 88.57% in the second cycle. Furthermore, student activity in cycle I got an average percentage of 61.42% and cycle II 85.71%. And writing student narrative essays was quite good, out of 22 students only 17 students or 77.27% achieved completeness individually. The results of writing student narrative essays in cycle II were also quite good with an average of 82.54 and out of 22 students there were 19 students or 86.36% who achieved completeness individually. Thus it can be concluded that by applying the mind mapping model it can increase teacher activity in teaching, increase student learning activities, and can improve the results of narrative essay writing skills for class IVA students of SD Negeri 002 Kunto Darussalam.